La climatisation des politiques dans un contexte de fragmentation et sectorialisation des agendas et de la mise en œuvre des instruments - Eduardo de Lima Caldas; Gilles Massardier (Confins)
This paper deals with policy making and implementation of policy instruments for Climate Adaptation of Agriculture (AACC) and fits into the literature concerning the challenges of efficient implemetation of climate policies in the territories. It describes the process of sectorization of the phenomenon, and analyzes the instruments which link agriculture to climate change in the State of São Paulo: the agroecological transition protocol and plan, and also the old rural insurance now "adapted" to climate risks.It concludes that: adaptation policies are weakly setted on the political agenda; the choice of policy instruments shapes the agenda; the marginalized agricultural sector creates its own adaptive, “acclimatized” and disjointed policies from other sectors, reinforcing their marginalization; the policy making of these instruments do not follow a sequential multi-level logic, from the international to the Union, the States and the municipalities; the instruments are not articulated between them, but suggest a sort of “tinkering” of sectoral policies, each with its own logic and processes.